(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The political challenges in Karnataka adherence to reform are evident with the introduction of new institutional mechanisms for managing infrastructure better. The government also declared that it was committed to offer good governance to the people of Karnataka. Hence, public dialogue was complemented by legislative action and administrative measures. The government tried to take people into confidence to make them accept the path of reform by creating a public debate and democratising the information regarding the fiscal position of the state. The general population of Karnataka were associated with two extensive scale political movements—one, territorial and the other, national. From one viewpoint, they took part effectively in the Congress development both pre-Gandhian and Gandhian, in driving the British out of the nation. Then again, they likewise sorted out effectively the Karnataka Ekikarana Movement or the Movement for Karnataka Unification, requesting that every one of the regions possessed by Kannadigas ought to be reconstituted into a solitary territory dependent on the guideline of one dialect one region.